Understanding Risky Credit Behavior In Paylater Usage: The Interplay Of Financial Literacy, Impulsive Buying, And Self-Control - Thania Kusmalinda; Setiyo Purwanto (UNIVED Press, 2026)
The rapid growth of PayLater services in the metropolitan city of Jakarta increases consumers exposure to the dynamics of consumptive financing. Financial literacy inequality and impulse buying tendencies have the potential to cause risky credit behavior in PayLater users. This research was conducted in 2025 using a quantitative method, using a measured questionnaire consisting of variables of financial literacy, impulse purchase, risky credit behavior, and self- control. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the structural relationships and moderation effects. The PayLater user population in the DKI Jakarta area is aged 18-45 years old with a purposive sample of 456 respondents who are actively using PayLater in the last six months. The results showed that financial literacy had a negative effect on impulse purchases (β = -0.28, p < 0.01). Impulse purchases were positively associated with risky credit behavior (β = 0.34, p < 0.001). Self-control acts as a moderation variable in the relationship between impulsive purchasing and risky credit behavior (interaction β = -0.12, p < 0.05), so that increased self-control weakens the impact of impulsivity on credit risk. Overall, financial literacy can suppress risk through reduced impulsivity, while self-control reinforces the benefits of literacy. These findings have practical implications for the PayLater platform, financial institutions, and financial literacy programs in Jakarta, in the form of higher financial literacy reducing impulsivity to purchase; impulsive buying increases risky credit behavior; self-control suppresses the impulsive effect on credit risk; financial literacy programs and increased self-control can reduce the level of credit risk in PayLater users.